2016
DOI: 10.1002/jctb.5116
|View full text |Cite
|
Sign up to set email alerts
|

A review of the potential of pretreated solids to improve gas biofuels production in the context of an OFMSW biorefinery

Abstract: The organic fraction of municipal solid waste (OFMSW), mainly composed of lignocellulosic polymers, is extremely complex. Therefore, it is necessary to apply pretreatments to remove the lignin content and decrease the cellulose crystallinity in order to use the OFMSW for gas biofuels production in the context of biorefineries from waste. This work focused on critically reviewing the conventional pretreatments applied to OFMSW, with the goal of improving the H 2 production, as well as other biofuels in modern b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 206 publications
(246 reference statements)
0
4
0
Order By: Relevance
“…Perera et al [55] arrived to similar observations than ours, arguing that the improvement in hydrogen production at temperatures above 25 °C is not defensible as net energy gains were negative and declining as temperature increased. Moreover, other strategies to increase the energetic gains of psychrophilic biohydrogen production would be by its coupling to other bioenergy processes such as microbial fuel cells, photofermentation and anaerobic digestion, among others [56][57][58][59].…”
Section: Please Insert Figure 3 Herementioning
confidence: 99%
“…Perera et al [55] arrived to similar observations than ours, arguing that the improvement in hydrogen production at temperatures above 25 °C is not defensible as net energy gains were negative and declining as temperature increased. Moreover, other strategies to increase the energetic gains of psychrophilic biohydrogen production would be by its coupling to other bioenergy processes such as microbial fuel cells, photofermentation and anaerobic digestion, among others [56][57][58][59].…”
Section: Please Insert Figure 3 Herementioning
confidence: 99%
“…Mild thermal pretreatment can, in fact, significantly alter both physical and chemical properties of FW, resulting generally in increased solubilization (Pagliaccia et al, 2016(Pagliaccia et al, , 2019Montecchio et al, 2017), in reduced lignocellulosic matrix, and improved digestate hygienization (Ariunbataar et al, 2015). Cellulose, hemicellulose and lignin containing wastes as OFMSW (source separated organic fraction) and FW (Romero-Cedillo et al, 2017), need further pretreatment in order to make the substrate more accessible to microbial degradation (Loow et al, 2016). Pecorini et al (2016) reported increase of soluble COD, carbohydrates and proteins concentration in the pretreated OFMSW sample, while lignocellulosic and starch fraction were found to be lower in the pretreated FW by Pagliaccia et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sources of biomass for biorefineries are numerous and in order to not compromise the food supply, biowastes should be mainly used as its substrates (Romero-Cedillo et al 2016). Considering that Mexico was the 11 th agriculture producer worldwide with an annual production of 210 million tons in 2018 (SADER 2019), its wastes generation along the food supply chains (production, postharvest, processing, distribution, consumption) are also considerable.…”
Section: Introductionmentioning
confidence: 99%